Mitotherapy: Unraveling a Promising Treatment for Disorders of the Central Nervous System and Other Systemic Conditions - Gabriel Nascimento-dos-Santos; Eduardo de-Souza-Ferreira; Rafael Linden; Antonio Galina; Hilda Petrs-Silva (Cells, 2021)
Mitochondria are key players of aerobic respiration and the production of adenosine triphosphate and constitute the energetic core of eukaryotic cells. Furthermore, cells rely upon mitochondria homeostasis, the disruption of which is reported in pathological processes such as liver hepatotoxicity, cancer, muscular dystrophy, chronic inflammation, as well as in neurological conditions including Alzheimer’s disease, schizophrenia, depression, ischemia and glaucoma. In addition to the well-known spontaneous cell-to-cell transfer of mitochondria, a therapeutic potential of the transplant of isolated, metabolically active mitochondria has been demonstrated in several in vitro and in vivo experimental models of disease. This review explores the striking outcomes achieved by mitotherapy thus far, and the most relevant underlying data regarding isolated mitochondria transplantation, including mechanisms of mitochondria intake, the balance between administration and therapy effectiveness, the relevance of mitochondrial source and purity and the mechanisms by which mitotherapy is gaining ground as a promising therapeutic approach.